IMPELEMNTASI PENDIDIKAN KHAS KEJOGJAAN (PKJ) SEBAGAI UPAYA PELESTARIAN KEARIFAN LOKAL DI SD NEGERI SURYODININGRATAN 3 YOGYAKARTA - Linda Istiharoh; Rian Nurizka (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Kejogjaan Special Education is a real action in the implementation and regulation of the Governor of the Special Region of Yogyakarta Number 66 of 2013 which prioritizes the interests that underlie local wisdom for students. This study aims to analyze the implementation of Kejogjaan Special Education as an effort to preserve local wisdom at SD Negeri Suryodiningratan 3 Yogyakarta, which can be seen from several aspects, namely through planning, implementation and influence of the Kejogjaan Special Education program as an effort to preserve local wisdom at SD Negeri Suryodiningratan 3 Yogyakarta. The method used in this study is a descriptive qualitative approach. Data were collected by means of observation, interviews, and documentation. The location of the study was at SD Negeri Surodiningratan 3 Yogyakarta with three sources, namely the principal, class teacher,and students of SD Negeri Suryodiningratan 3 Yogyakarta. The researcher's data analysis technique model used the three-flow activity model from Miles and Huberman, namely data reduction, data presentation, and drawing conclusions. The results of the study indicate that: 1) SD Negeri Suryodiningratan 3 Yogyakarta has planned and prepared the implementation of the Kejogjaan Special Education program and has been integrated into the 2024/2025 Education Unit Operational Curriculum (KOSP), 2) The formation of a Kejogjaan Special Education program development team, 3) The implementation of the Kejogjaan Special Education program as an effort to preserve local wisdom at SD Negeri Suryodiningratan 3 Yogyakarta has been carried out well through habits, habits and extracurricular activities by instilling the philosophical values of Kejogjaan Special Education (Hamemayu-mingsih bawana, Sangkan paraning dumadi, and Manunggaling Kawula Gusti) by the entire school community.